Numerical modeling of safety factor evaluation associated with the dredging and quarry mining techniques in northeast Bangladesh - Islam, Md. Rafiqul; Omar Faruque, Mohammed; Shahid, Abu Toyob; Hossain, Iqbal; Al Masum, Abdullah (International Journal of Advanced Geosciences, 2015)
This article describes the numerical modeling to investigate the safety factor of the quarry and dredging mining methods in the Volagonj area of Sylhet district in northeast Bangladesh. Two kinds of numerical models (A and B) are presented here. Both models consist of a single zone that includes gravelly sand deposits with some fine silt and clay. The zone also bears homogeneous rock/soil physical characteristics. Model A assumes safety factor of dredging mining method with variable slope angles and water column height of 40 m. Model B assumes safety factor of the quarry mining method associated with variable slope angles, where water column of the riverbed has not been considered. The numerical modeling results reveal that the safety factor of the model A ranges from 1.56 to 1.04. The safety factor ranges from 1.32 to 0.81 for model B. The calculated safety factor of the Volagonj rock quarry implies that the slope angle should not be greater than 70o for the dredging mining method. Because the critical safety factor values are 1.07 and 1.04 associated with slope angles 75o and 80o, respectively. For the case of the quarry mining, the appropriate slope angle also should not be greater than 60o.